PENINGKATAN SUMBER DAYA EKONOMI PEDESAAN MENUJU GLOBALISASI EKONOMI - Wijaya, Indra Adhi; Kuncoro, Amin (Jurnal Bulletin, 2017)
Increasing Rural Economic Resources Promoting Economic Globalization. This research is a test of action without research ie the researcher does not conduct systematic research in accordance with the rules of research methodology to know the problems, diseases, potential or strengths, weaknesses, opportunities and threat organizations. The formulation of the problem of this research is how the government efforts to improve the rural economy while the purpose of this research is to know the government's efforts in improving the rural economy, especially in the Village Jrahi Gunungwungkal District Pati. This research tries to annul a basic potency of rural economic resource in Pati Regency. Economic resources in Pati District, especially in Jrahi Village, Gunungwungkal District is a productive economic resource that has been dormant, or better known only to create raw materials, then from raw materials are distributed to those in need and then through a process with significant results. The result of this research is agriculture product, especially chocolate with high level of permentation, so that the value produced from the brown farm has a good value compared to chocolate in Indonesia. However, without the attention of the central government, then of course the agricultural products are inferior to products that already have brands in Indonesia